Penggunaan Technology Acceptance Model (TAM) Untuk Mengukur Kepuasan Mahasiswa STIE Bentara Persada Dalam Menggunakan Aplikasi Zoom Cloud Meeting - Laba, Sakeus (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2023)
The impact of the covid 19 pandemic has encouraged the use of the zoom cloud meeting application as a media to support online learning in the STIE Bentara Persada campus environment. In the new normal era until now the zoom cloud meeting application is also still used as a medium that supports the learning process, especially online lectures, webinars and online training for lecturers and students in the STIE Bentara Persada environment. The existence of the use of such applications encourages this research to be carried out with the aim of knowing the level of user acceptance of the zoom cloud meeting application in the dimensions of perceived ease of use, perceived usability, behavioral interest and actual use. This study also aims to determine and analyze the effect partially or simultaneously of perceived ease of use, perceived usefulness and behavioral intention variables on actual use. There were 71 samples in this study which were determined using the slovin formula and the sampling technique used was simple random sampling. The results of the research in the partial test of the perceived ease of use variable have a positive and significant effect with a t count of 2,677 > t table of 1,996, the perceived usefulness variable has a positive and significant influence on actual use with proof of the magnitude of the t count value of 3,682 > t table of 1,996 with a significance level of 0,000 < 0.05, and the behavioral interest variable in relation to the use variable actually has a positive and significant effect with a t count of 3.670 > t table of 1.996 and a significance value of 0.000 < 0.05. Simultaneously the variables perceived ease of use, perceived usefulness and behavioral interest have a positive and significant influence on the actual use variable by proving the value of F count 43.568 > F table 2.736 and a significance level of 0.000 < 0.05.